Reply to Berlanga et al. (DOI 10.1515/cclm-2014-0420) - Joannes F.M. Jacobs; Rein M.J. Hoedemakers; Henk te Velthuis (Clinical Chemistry and Laboratory Medicine (CCLM), 2014)
Lipoprotein X (LpX) is an abnormal lipoprotein-like particle occurring mainly in cholestasis, lecithin-cholesterol acyltransferase deficiency, post-transplant cholestatic liver dysfunction, hepatic graft-versus-host disease, and selected intravenous lipid emulsion or parenteral nutrition settings. Enrichment in phospholipids and unesterified cholesterol, paucity of cholesteryl esters and triglycerides, and usual absence of apolipoprotein B (apoB) challenge assumptions underlying routine laboratory testing. This review distinguishes analytical interference, in which LpX biases measurement procedures, from interpretative distortion, in which a valid cholesterol result no longer reflects the burden of atherogenic apoB-containing particles. Friedewald, Martin-Hopkins, Sampson, and other calculated LDL-cholesterol (LDL-C) equations cannot identify LpX and may retain its cholesterol in calculated LDL-C; direct LDL-C assays are also method dependent. We propose indicative, rather than diagnostic, screening triggers: in a compatible setting, total cholesterol (TC) ≥500 mg/dL (12.9 mmol/L) may be considered marked and ≥1,000 mg/dL (25.9 mmol/L) extreme; apoB within or slightly above the adult range, together with TC/apoB ≥8 mmol/g or non-HDL-C/apoB ≥7.5 mmol/g, should prompt verification. Confirmation may integrate free cholesterol and cholesteryl ester measurements, configured lipoprotein electrophoresis with filipin staining, apoB depletion, nuclear magnetic resonance, ultracentrifugation with an orthogonal method, or lipidomics. LpX appears less atherogenic than apoB-containing LDL but is not innocuous because xanthomatosis, hyperviscosity, and thrombotic complications may occur, while conventional atherogenic lipoproteins may coexist. ApoB-containing LpY and LpZ may attenuate cholesterol-apoB discordance. A structured LpX-oriented laboratory workflow can reduce misclassification of dyslipidaemia and pseudoelectrolyte disorders and support safer clinical decisions.